Stepping back to look ahead: neuter encapsulation and referent extension in counter-argumentative and causal relations in Spanish - Parodi, Giovanni; Julio, Cristobal; Nadal, Laura; Cruz, Adriana; Burdiles, Gina (Language and cognition, 2019)
In discourse comprehension, if all goes well, people tend to create a rich and coherent mental representation of the events described in the text. To do so, referential and relational coherence must be established in order to construct a connected discourse. The objective of this follow-up eye-tracking study (N = 72) is to explore the existence of an interaction effect between two factors: (a) the extension of the referent (short and long antecedent), and (b) the semantic relation (counter-argumentative a pesar de, and causal por), when processing the neuter pronoun ello in texts written in Spanish. No previous study has systematically compared the on-line processing of texts in which different extensions of the encapsulated anaphoric antecedent by the neuter pronoun ello (‘this’ or ‘it’ in English) are presented in diverse marked semantic relations (causal and counter-argumentative). Based on three eye-tracking measures, we found distinctive patterns of reading behavior when anaphoric neuter reference and semantic relations must be processed conjointly in order to construct a coherent mental representation. The main findings show that reading longer and more complex antecedents encapsulated by the neutral pronouns ello exerts more cognitive effort in late processing (Look Back measure), particularly when simultaneously and in the same discourse construction there is an explicitly marked counter-argumentative semantic relation. Implications for theories of referential and relational coherence are discussed.